Oclusión, emergencias-urgencias en el bucle teoríainvestigación en la administración (2019)
The present paper evidences the results of the degree work titled relationbetween the discourses of modernity and the complexity in the perspectives ofthe administrative thinking of the directors of the programs of administrationoffered in the universities of Pereira and the members of the network ofphilosophy theory And management education that expresses discussionsproposals that emerge from the reflection about the administration and froma constant dialogue from the feeling-think. It is evidence of a life project thatis shaped in the investigation of philosophical questions of administrativeorganizational thinking.